Identifying cultural heritage corridors for preservation through multidimensional network connectivity analysis — a case study of the ancient Tea-Horse Road in Simao, China. (2nd January 2021) - Li, Hui; Jing, Jing; Fan, Honghong; Li, Yanmei; Liu, Yang; Ren, Jiahao
ABSTRACT: Due to the development and evolution of transportation networks, and the destruction and disappearance of cultural heritage in the urbanisation process, it is imperative to protect historical and cultural heritage using various public policy tools. Identifying heritage sites is a critical first step in achieving subsequent successful preservation. However, few extant studies have explored methods to identify heritage corridors using network analysis approaches. This study uses multidimensional network connectivity analysis to identify cultural heritage corridors along the ancient Tea-Horse Road. Based on the theory of occurrence, this paper considers the hierarchical factors such as time, space, ethnic culture, religious culture, and altitude differences in landscape patches to explore how these corridors are connected through a multidimensional network. The study fills a void in current literature and presents a spatially integrated multidimensional approach identifying cultural heritage corridors, making it possible for the protection, preservation, and development of these corridors.